Dampak Pemberdayaan Perempuan terhadap Angka Kekerasan dalam Rumah Tangga (KDRT) di Provinsi Maluku Utara - Marnita Dahlan; Chairullah Amin; Amran Husen (Journal of Islamic Economics and Finance, 2025)
The government's efforts to reduce domestic violence (KDRT) in North Maluku Province have been carried out, among others, through the implementation of women’s empowerment programs. This study aims to examine whether the Gender Empowerment Index (IDG), Gross Regional Domestic Product (GRDP) percapita, women's involvement in home-based industries (IR), and the intensity of domestic violence socialization programs have a significant effect on domestic violence rates across districts/cities in North Maluku. This research utilizes panel data regression analysis with data spanning the years 2016–2024. The data were processed using Microsoft Excel and STATA14 software. The findings indicate that the increased participation of women in the economic and political sectors has not yet fully translated into a reduction in domestic violence, largely due to persistent social norms and patriarchal values within households. This suggests that economic factors alone are not sufficient to explain the prevalence of domestic violence. However, women's involvement in home-based industries was found to significantly improve their economic independence and bargaining power within the household. Furthermore, consistent government-led domestic violence awareness campaigns have proven effective in enhancing protection mechanisms for women at risk. In conclusion, the study finds that the Gender Empowerment Index (IDG) and GRDP per capita do not have a statistically significant impact on domestic violence rates. Conversely, women's participation in home-based industries and domestic violence socialization efforts are significantly associated with reductions in domestic violence in North Maluku Province.